Floods in a changing climate : hydrologic modeling - Mujumdar, P. P., 1958-; Nagesh Kumar, D. (Dasika), 1963- (Cambridge, UK. : Cambridge University Press, 2012)
'Various modeling methodologies are available to aid planning and operational decision making: this book synthesises these, with an emphasis on methodologies applicable in data scarce regions, such as developing countries. Problems included in each chapter, and supported by links to available online data sets and modeling tools, engage the reader with practical applications of the models. Academic researchers in the fields of hydrology, climate change, and environmental science and hazards, and professionals and policy-makers working in hazard mitigation, remote sensing and hydrological engineering will find this an invaluable resource. This volume is the second in a collection of four books on flood disaster management theory and practice within the context of anthropogenic climate change. The others are: Floods in a Changing Climate: Extreme Precipitation by Ramesh Teegavarapu, Floods in a Changing Climate: Inundation Modelling by Giuliano Di Baldassarre and Floods in a Changing Climate: Risk Management by Slodoban Simonovi{u28E2}--
'Hydrologic modelling of floods enables more accurate assessment of climate change impacts on flood magnitudes and frequencies. This book synthesises various modelling methodologies available to aid planning and operational decision making, with emphasis on methodologies applicable in data scarce regions, such as developing countries. Topics covered include: physical processes which transform precipitation into flood runoff, flood routing, assessment of likely changes in flood frequencies and magnitudes under climate change scenarios, and use of remote sensing, GIS and DEM technologies in modelling of floods to aid decision making. Problems included in each chapter, and supported by links to available online data sets and modelling tools accessible at www.cambridge.org/mujumdar, engage the reader with practical applications of the models'--
Includes bibliographical references and index.
Keywords: Hydrologic models -- Remote sensing; Flood forecasting; Flood damage prevention; Climatic changes -- Environmental aspects